Pengaruh Implementasi Good Governance, Pengendalian Internal, Moral Individu Terhadap Kecurangan (Fraud) Akuntansi Pada Badan Usaha Milik Desa (BUMDES) Se- Kecamatan Banjar - Ni Kadek Sri Utami Dewi; Nyoman Ayu Wulan Trisna Dewi (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This review plans to acquire tried illustrative discoveries about the impact of: 1) great administration on misrepresentation bookkeeping, (2) interior control on extortion bookkeeping, and (3) individual profound quality on extortion bookkeeping at BUMDES Kecamatan Banjar. The examination configuration utilized is a causal quantitative. The subject of this study were every one of the representatives in BUMDES Kecamatan Banjar, and the articles were: great administration, inward control, individual profound quality, and extortion bookkeeping. Complete populace of this exploration are 105 representatives who all join became perception unit, along these lines this examination including populace research. Information were gathered by utilizing a perception and meets, and broke down by way investigation. The aftereffects of this study are as per the following: (1) great administration have a positive and huge impact on extortion bookkeeping, (2) interior control has a positive and critical impact on misrepresentation bookkeeping, and (3) individual profound quality has a positive and huge impact on extortion bookkeeping at BUMDES Se-Kecamatan Banjar.